Enhancing the Purity of Reflective Structural Colors with Ultrathin Bilayer Media as Effective Ideal Absorbers. Issue 21 (2nd September 2019) - Yang, Zhengmei; Ji, Chengang; Liu, Dong; Guo, L. Jay
Abstract: Structural colors of high purity and brightness are desired in various applications. This study presents a general strategy of selecting the appropriate material and thickness of each layer to create high‐purity reflective colors in a classic asymmetric Fabry–Pérot cavity structure based on a dielectric–absorber–dielectric–metal multilayered configuration. Guided by the derived complex refractive index of the ideal absorber layer, an effective absorbing bilayer medium consisting of two ultrathin lossy films is used to improve the color purity of reflective colors by suppressing the reflection of its complementary colors with the enhanced optical absorption. Highly pure red, green, and blue reflective colors are designed and experimentally demonstrated employing different effective bilayer absorbers. Due to the high refractive index of the dielectric material, the colored structures exhibit great angle‐robust appearance (blue and red colors are up to ±60°, and green color is up to ±45°). The generalized design principles and the proposed method of using effective bilayer absorbers open up new avenues for realizing high‐purity thin‐film structural colors with more materials selections. Abstract : A general strategy for the material and layer thickness selection to produce high‐purity reflective colors in a dielectric–absorber–dielectric–metal multilayered structure is presented. The color purity of red, green and blue reflective colors can be significantly improved by designing different effective absorbing bilayer media to enhance the optical absorption over a broad wavelength range of nontargeted colors.